Toxicological evaluation and oral glucose tolerance test of ethanolic leaf extract of Barleria cristata L. in wistar albino rats - Narmadha, R.; Devaki, K. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: To evaluate the acute toxicity study and effective dose determination of ethanolic leaf extract of Barleria cristata L. Methods: Toxicological evaluation and effective dose determination of ethanolic leaf extract of Barleria cristata were performed in wistar albino rats. 250, 500, 1000 and 2,000 mg/kg of body weight of ethanolic leaf extract of Barleria cristata (EtBc) were administered orally as a single dose to rats. Rats were observed periodically for symptoms of toxicity and death within 24 hours and then daily for the next 14 days. So the rats were observed for another 14 days and then sacrificed to collect serum and organs for the analysis of biochemical parameters. After this study, rats were induced with diabetes by a single intra peritoneal injection of 45 mg/kg bodyweight of streptozotocin. Ethanolic leaf extract of Barleria cristata was orally administered to diabetic rats at 200, 400 and 600mg/kg doses for 7 days through oral glucose tolerance test (OGTT). Glycemic index was demonstrated the variable doses of ethanolic leaf extract in normal and diabetic rats during OGTT studies. Results: In acute toxicity study, the results were showed that the administration of the ethanolic leaf extract of Barleria cristata (EtBc) at all given doses (up to 2000 mg kg) did not produce any sign of acute toxicity or instant death in rats tested during the period of observation. From OGTT study, 400mg/kg dosage of EtBc exhibited notable blood glucose lowering effect at 90 min than the other doses and this was similar to that of standard drug glibenclamide treated rats. This dosage was showed the highest percentage of glycemic index in both normal and diabetic rats. Conclusion: EtBc was revealed the non-toxic nature used for acute toxicity studies and among various doses of this extract, 400 mg/kg brought an effective hypoglycemic activity in wistar albino rats.